The Relationship between Arm Muscle Strength and Hand-Eye Coordination on Underpassing Skills in Volleyball Extracurricular Students at SMK Taruna Satria Pekanbaru - Santy Santy; Daharis Daharis (Jurnal Olahraga Indragiri, 2023)
The purpose of this study was to determine the relationship between arm muscle strength and hand-eye coordination on the underhand passing skills of volleyball extracurricular female students at SMK Taruna Satria Pekanbaru. The type of research is correlation. The population and sample in this study were 14 extracurricular students at SMK Taruna Satria Pekanbaru. The research instruments used were arm muscle strength tests, hand eye coordination tests and underhand passing tests. The data analysis technique used is the correlation value test. Based on the results of research that has been conducted at SMK Taruna Satria Pekanbaru, in this case the following conclusions can be drawn: (1) There is a contribution of arm muscle strength to the results of lower passing in volleyball extracurricular students at SMK Taruna Satria Pekanbaru with a contribution amount of 0.224 with Low category. (2) There is a contribution of hand-eye coordination to the results of underhand passing in volleyball extracurricular students at SMK Taruna Satria Pekanbaru with a contribution amount of 0.180 in the Very Low category. (3) There is a contribution of arm muscle strength and eye-hand coordination to the results of underhand passing in volleyball extracurricular students at Taruna Satria Pekanbaru Vocational School with a contribution amount of 0.300 in the Low category and a percentage of 9%.